Covert operations : investigating the known unknowns - Carter, Claire C.; Phillips, Sandra S.; Priest, Dana (New Mexico : Radius Books, 2014)
Following the tragedies of September 11, 2001, contemporary artists such as Ahmed Basiony, Thomas Demand, Harun Farocki, Jenny Holzer, Trevor Paglen and Taryn Simon urgently pursued the complicated intersection of freedom, security, secrecy, power and violence. 'Covert operations: Investigating the known unknowns' features 13 international artists who have collected and revealed unreported information on subjects ranging from classified military sites and reconnaissance satellites to border and immigration surveillance, terrorist profiling, narcotics and human trafficking, illegal extradition flights and nuclear weapons. Among the other contributing artists are Anne-Marie Schleiner, Luis Hernandez Galvan, David Taylor and Kerry Tribe.
Covert Operations: Investigating the Known Unknowns, Museum of Contemporary Art, Scottsdale, September 28, 2014 trought January 11, 2015
boek